STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN OBJEK WISATA ALAM TELUK JERING DI KABUPATEN KAMPAR PROVINSI RIAU - ARWANTO HARIMAS GINTING; Data Wardana; Zainal Zainal (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
Abstract. This study aims to look at the government's strategy in the development of the Jering Bay Natural Tourism Object, Kampar Regency. This natural tourism object has a wide expanse of sand such as the beach, a stretch of green grass, forest plantation residents and lakes around the tourist sites. This tourist attraction is visited by tourists, especially on holidays. However, this natural tourist attraction has not received attention from the government. For this reason, researchers conduct research by looking at development strategies according to Cooper et al in Sunaryo (2013: 159) explaining that: a. The object of tourist attraction (Attraction) which is equipped with uniqueness and attraction based on nature, culture, and artificial / artificial. b. Accessible (Accessibility) which addresses the ease of transportation and the transportation system. c. Amenitas (Facilities) that complement tourism supporting and supporting facilities. d. Public facilities (Additional Services) that support tourism activities and e. institutions that have the authority, responsibility and role in supporting the implementation of tourism activities. This research was conducted in Jering Bay with qualitative research methods. While the data collection technique was carried out by field observations, interviews with informants namely the Kampar District government, manager of attractions, Village Heads, BPD Members, community leaders and visitors. The results showed that this attraction has a nature-based tourist attraction. It takes residence access and supporting facilities such as shelter, fostering local communities, and government support by regulating tourist areas and making regulations about the management of these attractions and supported with cultural activities and tourism activities. Key words: Government's strategy, natural tourism object, and development